Transformational leadership and employee’s career satisfaction: Role of psychological empowerment, organisational commitment, and emotional exhaustion - Syed Ali Raza,; Sara Qamar Yousufi, (Asian Academy of Management Journal, 2023)
Transformational leadership is essential for employees’ empowerment as it significantly enhances leadership qualities and increases employees’ satisfaction. Accordingly, the lack of comprehensive exploration and understanding has motivated us to examine the relationship between transformational leadership, psychological empowerment, organisational commitment, career satisfaction, and the moderating role of emotional exhaustion. The objectives of this study are (1) to study the relationship between transformational leadership, psychological empowerment, organisational commitment, and career satisfaction of employees, (2) to evaluate the mediating role of psychological empowerment and organisational commitment in relationship between transformational leadership and career satisfaction, and (3) to evaluate moderating role of emotional exhaustion on relationship between transformational leadership, psychological empowerment, and organisational commitment. Data was collected via cross-sectional structured questionnaires by 513 bank employees. Results indicate that transformational leadership significantly relates to empowerment and organisational commitment of employees but is insignificantly associated with career satisfaction. Moreover, transformational leadership significantly influences employees’ career satisfaction through the mediation of empowerment and commitment. Moderation analyses revealed that higher emotional exhaustion weakens employees’ empowerment and transformational leadership, which further weakens the direct relationship between transformational leadership and psychological empowerment and association between transformational leadership and commitment. This research can assist managers in developing retention strategies for employees to enhance psychological empowerment, organisational commitment, and career satisfaction of employees.